Updated Lagrangian formulations of two hexahedral elements with rotational DOFs. Issue 2 (4th March 2018) - Zouari, Wajdi; Hammadi, Fodil; Assarar, Mustapha; Ayad, Rezak
ABSTRACT: Updated Lagrangian formulations of two eight-node hexahedral solid elements with rotational degrees of freedom (DOFs) are developed to analyse geometrically nonlinear large deflection problems. These two elements are based on the so-called Space Fibre Rotation (SFR) concept that considers fictive small rotations of a nodal fibre within the element to enrich the displacement vector approximation of low-order finite elements. The validity and efficiency of the proposed formulations are demonstrated by solving several nonlinear large deflection benchmarks and the obtained results show a much better accuracy than those based on the total Lagrangian approach.